Real-time control of triglide robot using sliding mode control method - Aydin, Muhammet; Yakut, Oguz (Emerald Group Publishing Ltd, 2018)
Purpose - The purpose of the study is to design a three-dimensional (3D) triglide parallel robot with a different approach and to control the manufactured robot via sliding mode control method that has not been applied to the robot before. Design/methodology/approach - The x,y and z coordinates of the end effector of the robot have been given as a reference. The x, y and z reference values are transformed as new reference values of the vertical movement of the robot on the endless screw by using the inverse kinematic equations of the robot. The control of the robot over these reference values is provided by a sliding mode control. The MATLAB/real-time toolbox has been used for creating the interface. The real-time control of the triglide robot has been carried out with a sliding mode controller in the Simulink environment. Findings - When the results of the sliding mode control are examined, it is seen that the desired reference values are provided in about 0.6 s. The velocity of the sliding limbs in each arm of the robot is approximately 50 mm/s. The reference values have been reached using the sliding mode control method, with an average error of 0.01 mm. In addition, the problem of chattering in the system caused by using the sign function has been relatively eliminated by using the saturation function instead of the sign function. Thus, the sliding mode control method with saturation function is more feasible. Originality/value - In this study, the triglide parallel robot was manufactured using a 3D model after taking into consideration the dimensions of the 3D model. After production, the necessary hardware connections were provided, and a real-time sliding mode control method was implemented to the robot by using the interface program in MATLAB/ Simulink environment. The literature contribution of the paper is the real-time control of the triglide robot with the sliding mode control method.
Keywords: Manufacturing; Sliding mode control; Design; Kinematics; Triglide parallel robot